Suppressing the Migration of Human Breast Cancer Cell Line by Targeting VAMP3 with miR-199a-3p - Nouf N. Laqtom,; Khloud M. Algothmi, (Journal of King Abdulaziz University: Medical Sciences, 2023)
Deregulation of microRNAs contributes to multiple processes in cancer growth and progression. miR-199a-3p is decreased in highly metastatic breast cancer cells, MDA-MB-231, and its ectopic expression has a potent antimetastatic effect on these cells. However, the mechanism by which miR-199a-3p mediates its antimetastatic function has yet to be elucidated. Because miR-199a-3p reduces the expression levels of its target genes, it is likely to observe an inverse association between miR-199a-3p and its prometastatic target genes at the expression level. The current work determines that the Vesicleassociated membrane protein 3 (VAMP3) expression is increased in highly metastatic breast cancer cells compared to less metastatic cells, Michigan Cancer Foundation-7. The ectopic expression of miR-199a-3p strongly inhibits VAMP3 Messenger RNA and protein in vitro. Herein, it is confirmed that two sites within the 3'-untranslated sequence of VAMP3 Messenger RNA are actively targeted by miR-199a- 3p, discovering a new regulatory mechanism for VAMP3 expression. Functional studies reveal that the suppression of VAMP3 contributes to miR-199a-3p antimetastatic effect, particularly cellular migration in vitro. In conclusion, these results indicate that miR-199a-3p targeting of VAMP3 possesses a significant potential impact in preventing or curing metastatic breast cancers.